PENGARUH PENGETAHUAN PAJAK DAN PERSEPSI WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Supriyati Supriyati (The Indonesian Accounting Review, 2011)
The Directorate General of Taxation has done a strategic role. One of the activities is to increase the tax payer's compliance. This research attempts to see the influence of tax knowledge, tax payer perception of 'fiscus" and criterions of tax payer of complionce toward tax payer compliance. The procedure of data collection in this research is by distributing tie questioniaires to the tax payers in Tax Services Department of East Sidoarjo directly in 2007. The researchers have collected 43 questioners. The result of validity and relrability from 44 questions shows that all questions are valid and reliable. Accordingly, the result of normally shows that data is in a normal distribution. The result of regression shows that just tax knowledge variable infiuences significantly the tax payer's compliance. From the result of this research, it is expected that the next researchers and academicians can provide tax knowledge for the students from the low level of education to the higher levei of education. The Diiectorate General of Taxotion should also increase their quality of services.